Ideology in Literary Translation, or What Is, After All, “The White Man’s Burden”? - Kamovnikova, Natalia (Respectus Philologicus, 2015)
A literary translation invariably reflects the historical and cultural features of the time and place of its production. The perception of literary texts is determined by the political and cultural situation in a given language community, and the literary translation, therefore, is justly seen as the negotiation that aims at reaching a compromise between two languages, two geographical spaces, and two historic times. Literary translation is as well regarded as a manipulation, an attempt to make the translation fit in with the target audience culture, social situation, or ideology. The famous poem The White Man’s Burden by Rudyard Kipling was alternately seen as racist and Eurocentric or as missionary and philanthropic. The translations made into different European languages conveyed the ideology of the poem differently as well, the interpretation depending on the historic time, the targeted language community, and the social requirements to literature and translation. These social factors preconditioned the difference in interpretation of such controversial issues of the poem as race, difference, and religion in the five translations analysed in this article. The article offers a comparative study of the strategies applied by Russian, Bulgarian, and French translators of the poem who worked under different historical and social conditions.